U–Pb geochronology reveals evidence of a Late Devonian hydrothermal event, and protracted hydrothermal–epithermal system, within the Mount Painter Inlier, northern Flinders Ranges, South Australia. Issue 7 (2nd October 2020) - Hore, S. B.; Hill, S. M.; Reid, A.; Wade, B.; Alley, N. F.; Mason, D. R.
Abstract: The Mount Gee Sinter and the Radium Ridge Breccia within the Mount Painter Inlier, South Australia, preserve evidence of a hydrothermal event peaking during the Late Devonian ( ca 365 Ma). Prior to this study, limited data relating to this event were available, but our results of 846 LA-ICPMS U–Pb monazite analyses indicate the timing of this hydrothermal event. The dominant monazite population age of ca 363 Ma for the Mount Gee Sinter represents earlier phases of a protracted hydrothermal–epithermal system, whereas a later epithermal phase cross-cuts rocks hosting ca 220 Ma age zircon. Parts of the Radium Ridge Breccia have been recently interpreted as a series of Early Cretaceous glacial events. Zircon ages (604 zircon analyses) from the Radium Ridge Breccia define a detrital population dominated by ca 1585 Ma ages, consistent with derivation of clasts within the breccia from local granitic and metasedimentary basement. The Radium Ridge Breccia is, however, dominated by a ca 367 Ma aged monazite population, probably reflecting overprinting of the local Mesoproterozoic granitic basement rock during the same hydrothermal event as formed the earlier phase of the Mount Gee Sinter. It is interpreted that the monazite ca 365 Ma age reflects a significant Late Devonian hydrothermal event, evidenced locally in the southern Mount Painter Inlier, resulting from localised heat flow but with thermal implications for the regional geology of the northwestern Curnamona Province.